Characteristics of the subscription revenue model used in SaaS applications - Turunen, Helinä (2012)
Turunen, Helinä Characteristics of the subscription revenue model used in SaaS applications Jyväskylä: University of Jyväskylä, 2012, 22 p. Information Systems, Bachelor’s Thesis Supervisor: Ojala, Arto Cloud service and cloud business have increased tremendously in the last few years. Both the technology and business aspect of cloud services have been studied widely, especially the advantages of cloud computing from the cus-tomer perspective. Cloud service pricing and its characteristics have been stud-ied less than the technology and business models, and this thesis concentrates on the characteristics, advantages and disadvantages of the subscription model used in Software as a Service (SaaS) applications. The thesis is based on a literature review conducted by using various academic article databases such as IEEE Explore and ACM Digital Library. The research was conducted by using academic articles and up-to-date Internet resources. Among the principle findings of this research is that the characteristics of the subscription model are closely related to the already know characteristics of cloud services. The most surprising finding was how using the subscription model motivates the software developers to create better software faster and more efficiently when compared to traditional software models. From the customer point of view, a negative finding was the possible customer lock-in effect caused by the subscription model together with the SaaS delivery model, as the combination might cause enormous switching costs should such a change be required. The profitability of the subscription model should be analyzed from the customer perspective as well as the provider perspective. This should be done with a view to reducing the negative aspects and increasing customer satisfaction even further.